Efeito da Faseolamina sobre parâmetros bioquímicos gerais e oxidativos do coração de ratos diabéticos induzidos por STZ - Oliveira, Renato José da Silva (2010)
Cardiovascular complications of diabetes mellitus are associated with oxidative stress that occurs as a result of the disarrangement between the production of reactive oxygen species (ROS) and their neutralization by antioxidant systems under hyperglycemia. The exacerbated production of ROS may contribute to increased cardiac collagen content, collagen glycation in consequence of the formation of advanced glycation end products (AGEs). These mechanisms are proposed to explain the increase in cross-linking and increased stiffness of the myocardium in patients with diabetes. Phaseolamin inhibits pancreatic alpha-amylase, which leads to a reduction on hyperglycemia. The aim of this study was to evaluate the protective effects of Phaseolamin in the cardiac tissue against damage of streptozotocin (STZ)-induced diabetic rats under oxidative stress levels and collagen type I deposition in vivo. Animals were distributed in six groups: non-diabetic (ND); non-treated diabetic (NTD); groups treated with commercial Phaseolamin at 100, 500 and 1500 mg/kg (D100, D500 and D1500 respectively); group treated with acarbose at 25 mg/kg (DACA). Treatments were given once daily by gavage during 20 days.The total antioxidant activity measured in NTD group was lower (p<0.001) when compared with ND animals and greater in diabetic patients who received treatment with acarbose and Phaseolamin (p<0.001).The enzymatic defense system represented by catalase (CAT) and superoxide dismutase (SOD) increased its activity in NTD group (p<0.001). The activity of SOD and CAT decreased after treatment with Phaseolamin (D100, D500, D1500 and DACA). The tissue damage caused by lipid peroxidation was reduced in D1500 (p<0.05), although it was increased to other groups (p<0.001). Phaseolamin treatment reduced the hyperglycemic state (16-42%) and decreases the formation of ROS, preventing the exacerbation of the antioxidant system in this tissue. Our study showed significantly increased deposition of collagen in all diabetic groups compared to ND rats. Groups D1500 and DACA showed reduced values of type I collagen compared to NTD group (p<0.001). In our experimental model, treatment with Phaseolamin prevents the development of ROS and myocardial collagen changes in diabetic rats. We suggest that Phaseolamin can be a complementary treatment for diabetes reducing the appearance of heart complications.